Desenvolvendo a liderança nos processos de manufatura: um estudo de caso - Povrosnek, Marcos Rogelho (2023)
The topic of leadership has aroused interest among scholars for centuries (Fiedler, 1967), but, it began to be studied in more detail at the early of the 20th century, when various lines of study emerged, such as trait theory, situational leadership, contingency, transactional, transformational, among others. In times of change, leadership is responsible for directing teams só that they meet new demands. Therefore, it is important for the organization to have a clear definition of the leadership profile it desires for its leaders, in addiction to understand the profile of its current leaders. In this sense, the research aimed to identify the level of convergence of the leadership profile of production leaders in the Stamping Area, represented by leaders at the tactical and operational levels (TOL), in relation to the leadership profile advocated by Strategic Management represented by leaders at the strategic level (SL), of the Bemetal company, from 2021 to April 2023. The methodology used to achieve the general objective was a simple case study strategy, with data collection being carried out through 16 video interviews, whit Bemetal’s TOL and SL leaders, who answered questions from a semi-structured guide focused on topics relevant to leadership. As an analytical category in the present study, leadership was understood as the ability to influence people to carry out tasks in order to achieve goals. The leadership styles used as reference were the transactional and transformational leadership styles based on Burns (1978) and Bass (1985). By carrying out thematic content analysis, with semantic categorization of company documents, interview transcriptions, and direct observation notes, it was possible to identify the conceptual perception of leadership and the role of the leader for both TOL and SL. It was also evident that the transactional leadership style reflects the current profile of TOL leaders, as they focus on carrying out process; and that the SL idealizes that the leaders have a profile align with the transformational leadership style, with a focus on people through investments in training for this purpose, where topics such as selfknowledge, emotional intelligence, and communication are highlighted as skills to be developed during the exercise of leadership. The research results also showed that external aspects of the organization’s business, such as seasonality, impacted the leadership development strategies promoted by the organization. Finally, the collected and analyzed information made it possible to achieve the objectives established by the research and present a theoretical-empirical model that can be used in future research.